Beyond Aesthetics. The Strategic Role of Art and Design in Renewing Italian Corporate Spaces - Marzia Tomasin (Pad)
This article explores the emerging role of art and design in Italian workplaces, highlighting how their integration redefines professional spaces, enhances employee well-being, and boosts company performance. The research offers insights into this evolving phenomenon by examining case studies and recent trends. It shows how workplace art and design have evolved from aesthetics to strategic assets. Examples like Pirelli’s Art at Work project and Lavazza’s corporate museum illustrate how this integration can significantly improve employee satisfaction and productivity. The concept of cultural welfare emerges as a key theme. The article also assesses the impact on ESG reporting and sustainability, confirming that art and design integration is becoming essential in corporate social responsibility strategies. Looking ahead, the study explores future prospects and challenges, arguing that this integration represents a transformative paradigm with the potential to alter physical environments, organizational dynamics, and social impact. Bridging theory and practice, the study contributes to the literature on cultural welfare and organizational aesthetics, offering strategies for companies to enhance work environments and corporate culture while aligning with global workplace design and responsibility trends.